STRATEGY AND POLICY INCREASING HUMAN DEVELOPMENT INDEX OF MANGGARAI REGENCY 2016-2021 - Salesman, Frans; Tapung, Marianus Mantovanni; Setiawan, Leonadus Ino (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
AbstractÂ The Human Development Index (HDI) is a composite index: health indicators through life expectancy, education indicators through mean expectations and school length, and per capita real purchasing power. The HDI level of NTT province in 2016 is 63.13 points, and Manggarai District in the same year amounted to 61.87 points. When compared with the national HDI, HDI Kabupaten Manggarai is still low. Therefore, it is necessary to develop Manggarai HDM strategy and policy during 2016-2021.Purpose. Develop strategies and policies to improve the Human Development Index in Manggarai 2016-2021. Methods. Analyzing Data publication BPS East Nusa Tenggara Â and Manggarai District 2014-2016, health profile of Manggarai District. Qualitative data obtained from the FGD preparation of Medium Term Development Plan Manggarai District 2016-2021. 42 FGD participants 42 persons. Results. The development of economic, education and health development strategies and policies that can accelerate the growth of HDI in Manggarai district during 2016-2021. Conclusion.IPM in Manggarai district has been in the